Memórias docentes: os impactos do ensino remoto na formação inicial de professores do curso de Pedagogia ICSEZ/UFAM - Marinho, Beatriz da Silva (Brasil, 2024)
This article establishes as a theme and source of study the “Teaching Memories: the impacts of remote teaching in the initial training of teachers in the pedagogy course – ICSEZ/UFAM”. In order to identify the methodological strategies used by students and teachers of the Pedagogy in Remote Education course Emergency (ERE); as well as, describe the formative experiences lived by these students in the context pandemic, in the same way that it intends to present the challenges and significant changes in the lives of future people teachers of the Pedagogy Course. The study is constituted through reading articles, books and theses. Characterized as qualitative research with a phenomenological approach and the technique of data collection used the form created by google forms and the semi-structured interview with the students of the Pedagogy course, who entered the university during the Covid-19 Pandemic. This way, To meet the objectives established in this research, we have the memory reports of 6 (six) students for analyze the questions that were relevant in the daily lives of academics during the pandemic. With the analysis of this research, the conflict experienced is noted, given the reality presented, raising some factors that resulted from the pandemic, such as the initial lack of communication between the university and academics; to the complications with the subjects provided in remote education and social issues due to personal issues of each student.